Governance of global value chains after the Covid-19 pandemic: A new wave of regionalization?. Issue 3 (July 2021) - Pla-Barber, José; Villar, Cristina; Narula, Rajneesh
The disruption of the trade and investment activities of multinational enterprises as a consequence of the Covid-19 pandemic has reinvigorated the debate on the configuration of global value chains (GVCs) as well as the risks and challenges associated with offshoring. This article depicts how the pandemic might affect GVC configuration by driving a trend toward a more regional footprint in industries in which resilience and reliability are critical. Such a shift would create new opportunities for reshoring, and affect both the types of upgrading trajectories and the governance systems in value chains. The article also draws from the intersection of the global-strategy and value-chain fields to propose potential topics and avenues for further research related to these trends. JEL Classification : M16, M21, M14